MODEL LKS FISIKA MATERI KALOR DAN PERUBAHAN WUJUD BERPENDEKATAN SAINTIFIK UNTUK MENGEMBANGKAN KARAKTER SISWA SEKOLAH MENENGAH ATAS - Yulianti, Dwi; Sartiyah, Sartiyah (Jurnal Penelitian Pendidikan, 2016)
Permendikbud number 65 of 2013 stipulates that the process of learning in the curriculum implemented in 2013 through a scientific approach. The Government has launched a character education in every level of education that is integrated into subjects. Worksheets on curriculum integrates character education in 2013 have not been in it, so there needs to be an example of character worksheets that implements scientific approach to curriculum 2013 The purpose of this study is to obtain worksheets, determine eligibility and level of legibility, knowing the increase in cognitive learning outcomes, and to know the character development of students. The method in this study is an R & D (Research and Development). The study procedures include: (1) introduction, (2) design, (3) the development or testing of the product. The test results showed that the feasibility of LKS is very suitable to be used as a means of learning physics and easy to understand because the value of high legibility. Improved cognitive learning outcomes of students who have learning using worksheets higher than students who received learning without LKS. LKS can also develop the character of students in particular disciplines, honest, curious, and communicative.